Preparation method of Ni-MWCNTs / MXene composite material for in-situ regulation and control of growth of CNTs

Through electrophoretic deposition and CVD in situ growth technology, the nickel ion content and CNTs pipe diameter of Ni-MWCNTs/MXene composite materials are regulated, and the problem of self-stacking and impedance matching mismatch of small-layer MXene during assembly is solved, achieving efficient Microwave absorption performance.

CN119300331APending Publication Date: 2025-01-10NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411197109.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the existing MXene-based absorbing materials, the small layers of MXene are prone to self-stack and aggregation during assembly, resulting in limited absorption performance and impedance matching mismatch, affecting its electromagnetic properties and microwave absorption performance.

Method used

The Ni-MWCNTs/MXene composite material is regulated by electrophoretic deposition and CVD in situ growth. By controlling the voltage and electrolyte concentration, the nickel ion content and CNTs pipe diameter are adjusted to achieve excellent wave absorption performance of the composite material.

Benefits of technology

The excellent absorption performance of Ni-MWCNTs/Ti3C2Tx composite material is achieved, the reflection loss reaches -37.94dB, the effective absorption bandwidth is 1.54GHz, and the dielectric imaginary part and dielectric loss are improved by regulating the CNTs pipe diameter, and microwave absorption is improved. Wave performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300331A_ABST
    Figure CN119300331A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of microwave absorbing materials, and relates to a preparation method of a Ni-MWCNTs / MXene composite material for in-situ regulation and control of growth of CNTs. The invention discloses a preparation method of a Ni-MWCNTs / MXene composite material for in-situ regulation and control of growth of CNTs, and the preparation method comprises the following steps: by taking a few-layer Ti3C2Tx dispersion liquid as an electrolyte, a nickel sheet as a working electrode and a graphite electrode as a counter electrode, applying 0.1-3V voltage, depositing for 1-20 hours, and carrying out CVD in-situ growth to obtain the Ni-MWCNTs / Ti3C2Tx composite material. The invention further discloses the Ni-MWCNTs / MXene composite material for in-situ regulation and control of growth of the CNTs, Ni particles and carbon nanotubes are loaded on the Ni-MWCNTs / MXene composite material, the average particle size of the Ni particles is 10-30 nm, and the average tube diameter of the carbon nanotubes is 20-50 nm. According to the Ni-MWCNTs / Ti3C2Tx composite material and the preparation method thereof, a catalytic strategy of adsorbing metal ions through electrophoretic deposition is adopted, few layers of Ti3C2Tx are used as an electrolyte, in-situ regulation and control growth of CNTs is carried out on MXene, and the Ni-MWCNTs / Ti3C2Tx composite material with the excellent wave absorbing performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microwave absorbing materials and relates to a method for preparing a Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs. Background Art

[0002] The rapid development and widespread use of radio communications and electronic devices have led to increasingly serious electromagnetic wave pollution, which is not only threatening human health, but also interfering with precision instruments and information security. Therefore, it is urgent to study advanced electromagnetic wave absorbing materials to cope with complex electromagnetic environments.

[0003] Compared with other two-dimensional materials, such as COFs, MOFs, two-dimensional transition metal sulfides (TMD), hexagonal boron nitride, and graphene, two-dimensional transition metal carbides (MXenes) have the advantages of large specific surface area, wide absorption, adjustable rich surface functional groups, and metal-like conductivity, which makes them have great application prospects in microwave absorbing materials. In recent years, although MXene has been widely studied, its overall microwave absorption performance is greatly limited due to its relatively simple microwave absorption mechanism, high relative complex dielectric constant, and low relative complex magnetic permeability. In order to further improve the microwave absorption performance and adaptability, researchers have obtained MXene-based composite materials by regulating the composition and structural design to obtain excellent microwave absorbing materials. For example, heterogeneous interface structure, dielectric-magnetic synergy, porous structure, etc. Carbon-based materials are common high dielectric loss materials. They also have interface characteristics, stability, and light weight. They are often used to prepare a large number of heterogeneous interfaces and high conductivity loss MXene / carbon-based composite materials to enhance the microwave absorption performance of MXene. Carbon materials mainly include one-dimensional carbon nanotubes, two-dimensional graphene, and three-dimensional carbon nanospheres. Among them, the composite materials of one-dimensional carbon nanotubes are more prominent in constructing conductive networks and conduction losses, and can contribute stronger conductive losses and polarization losses with lower mass. In order to further improve the electromagnetic properties and impedance matching of MXene. Che et al. studied the preparation of magnetic CNTs / Ni heterostructure decorated MXene substrates by in-situ induced growth, and the minimum reflection loss was -56.4dB at 2.4mm. Zhang et al. prepared RGO / MXene / Fe3O4 microspheres by ultrasonic spraying technology, and used dielectric-magnetic synergy and three-dimensional porous structure to achieve a minimum reflection loss of -51.2dB at a thickness of 2.9mm. It is worth noting that most of the current reports on MXene-based absorbing materials are mainly multilayer MXene, and the research on single-layer or few-layer MXene is relatively small. The main problem currently faced is that few-layer MXene is prone to self-stacking and aggregation during the assembly process, and impedance matching mismatch affects its absorbing performance. Summary of the invention

[0004] The purpose of the present invention is to solve the above problems in the prior art and propose a method for preparing a Ni-MWCNTs / MXene composite material based on in-situ controlled growth of CNTs by using a few-layer Ti3C2T x Dispersion, in situ growth of CNTs by electrophoretic deposition and CVD.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing a Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs, comprising:

[0007] Few-layer Ti3C2T x The dispersion was used as the electrolyte, the nickel sheet was used as the working electrode, and the graphite electrode was used as the counter electrode. A voltage of 0.1 to 3 V was applied. After deposition for 1 to 20 h, Ni-MWCNTs / Ti3C2T was grown in situ by CVD. x Composite materials.

[0008] The voltage applied during the electrophoretic deposition process determines the dissolution rate of the anode nickel sheet and the size of the nickel ions. If the voltage is too high, the concentration of dissolved nickel ions will be too high and the ion radius will increase in the same time, resulting in a high content of nickel ions adsorbed between layers, an increase in the number of sites for catalytic growth of CNTs, and an increase in the diameter of CNTs. If the voltage is too low, the concentration of dissolved nickel ions will be too low and the ion radius will decrease in the same time, resulting in a low content of nickel ions adsorbed between layers, a decrease in the number of sites for catalytic growth of CNTs, and a decrease in the diameter of CNTs.

[0009] Preferably, the method for preparing the Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs comprises: x The dispersion was used as the electrolyte, the nickel sheet was used as the working electrode, and the graphite electrode was used as the counter electrode. A voltage of 1 to 2 V was applied. After deposition for 1 to 20 h, Ni-MWCNTs / Ti3C2T was grown in situ by CVD. x Composite materials.

[0010] Preferably, the few-layer Ti3C2T x The preparation method of the dispersion comprises: etching the MAX phase Ti3AlC2 with an in-situ hydrofluoric acid solution, centrifuging a multi-layer Ti3C2T x ;

[0011] Multilayer Ti3C2T x Mix with water, and then remove by ultrasonic and centrifuge to obtain a few layers of Ti3C2T x Dispersion.

[0012] More preferably, the in-situ hydrofluoric acid solution consists of 10-200 ml of hydrochloric acid with a concentration of 1-20 mol / mL and 0.8-12 g of LiF.

[0013] More preferably, the etching time is 1 to 48 hours, the rotation speed is 100 to 2000 rpm, and the temperature is 35 to 45°C.

[0014] More preferably, the few-layer Ti3C2T x The concentration of the dispersion is 1 to 20 mg / mL.

[0015] More preferably, the few-layer Ti3C2T x The concentration of the dispersion is 2 to 5 mg / mL.

[0016] More preferably, the few-layer Ti3C2T x The preparation method of the dispersion comprises:

[0017] S1. Slowly add 0.4-6 g of MAX phase Ti3AlC2 into in-situ hydrofluoric acid composed of 10-200 ml of concentrated hydrochloric acid with a concentration of 1-20 mol / mL and 0.8-12 g of LiF, and etch with magnetic stirring for 1-48 h at a rotation speed of 100-2000 rpm and a temperature of 35-45 °C;

[0018] S2, the etched liquid was centrifuged and washed with water until the pH value of the upper clear liquid was 5-7, and the bottom sediment multilayer Ti3C2T x ;

[0019] S3, multilayer Ti3C2T x After adding into deionized water, ultrasonication was performed in a constant temperature water bath (-4°C) in circulating condensed water for 0.5-5 h, and the upper black liquid was centrifuged to obtain a few-layer Ti3C2T x Dispersion.

[0020] Preferably, the CVD in-situ growth comprises: exhausting the air in the CVD tube furnace with an inert gas, first performing a first stage of heating, and then performing a second stage of heating; obtaining Ni-MWCNTs / Ti3C2T x Composite materials.

[0021] More preferably, the heating rate in the first stage is 1-20°C / min, the insulation temperature is 300-600°C, and the insulation time is 10-120min.

[0022] More preferably, N2 and H2 are passed during the first stage of heating, with flow rates of 100-500 sccm and 10-100 sccm respectively.

[0023] More preferably, the total flow rate of N2 and H2 in the first stage of heating is 100 to 300 sccm.

[0024] More preferably, the heating rate in the second stage is 5-20°C / min, the insulation temperature is 400-700°C, and the insulation time is 60-480min.

[0025] More preferably, the second stage insulation temperature is higher than the first stage insulation temperature.

[0026] More preferably, in the second stage of heating, N2, H2, and C2H2 are passed through, and the flow rates are 10-200 sccm, 10-100 sccm, and 10-100 sccm, respectively; and the pressure in the CVD tube furnace is 1×10 4 ~1×10 5 pa.

[0027] More preferably, the total flow rate of N2, H2, and C2H2 in the second stage of temperature rise heating is 100 to 300 sccm.

[0028] The invention also discloses a Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs.

[0029] Preferably, the Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs is loaded with Ni particles and carbon nanotubes, wherein the average particle size of the Ni particles is 10 to 30 nm, and the average tube diameter of the carbon nanotubes is 20 to 50 nm.

[0030] Preferably, the reflection loss of the Ni-MWCNTs / MXene composite material for regulating in-situ growth of CNTs is -10 to -50 dB at a thickness of 2.47 mm.

[0031] Further preferably, the reflection loss of the Ni-MWCNTs / MXene composite material for regulating the in-situ growth of CNTs is -37.94 dB at a thickness of 2.47 mm, and the effective absorption bandwidth is 1.54 GHz.

[0032] A microwave absorbing material comprises a Ni-MWCNTs / MXene composite material of CNTs grown by in-situ controlled growth of CNTs.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The present invention adopts the electrophoretic deposition adsorption metal ion catalysis strategy and utilizes a few-layer Ti3C2T x As an electrolyte, CNTs were grown in situ on MXene to obtain Ni-MWCNTs / Ti3C2T with excellent microwave absorption performance.x Composite materials.

[0035] 2. The electrophoretic deposition process of the present invention controls the dissolution rate of nickel and the thickness of MXene deposition by changing parameters such as voltage and electrolyte concentration to obtain Ni with adjustable nickel ion content and uniform dispersion. 2+ -MXene, which facilitates the subsequent CVD growth and regulation of the diameter of carbon nanotubes CNTs.

[0036] 3. The present invention uses in-situ hydrofluoric acid solution to etch, centrifuge and ultrasonicate the MAX phase Ti3AlC2 to obtain a few-layer Ti3C2T x Compared with hydrofluoric acid (HF) etching, in-situ hydrofluoric acid etching is safer, and during the in-situ hydrofluoric acid etching process, lithium ions will be intercalated into the interlayers of MXene, which is conducive to the exfoliation into a few-layer MXene. However, after the hydrofluoric acid etching exfoliates the few-layer MXene, some intercalating agents need to be added to complete it, which is more complicated and cumbersome.

[0037] 4. The present invention adopts two-stage heating in the CVD in-situ growth. The first stage is to completely reduce the nickel ions between the MXene layers to nickel elements, and the second stage is to provide a stable temperature for the growth of CNTs and better grow CNTs. The two-stage heating can better exert the catalytic effect of nickel particles.

[0038] 5. The present invention controls the pressure and total gas flow rate in the CVD tube furnace during the two-stage heating during CVD in-situ growth. The pressure will affect the temperature of C2H2 cracking and growing CNTs. When the pressure in the tube furnace decreases, the temperature of C2H2 cracking and growing CNTs will decrease, while too high a temperature will make MXene more easily oxidized. Controlling the total gas flow rate is beneficial to ensuring reaction stability.

[0039] 6. In the second stage of heating in the CVD in-situ growth, N2, H2 and C2H2 are passed through the system, wherein N2 is used as a protective gas to prevent MXene oxidation during the in-situ growth of CNTs; H2 is used as a reducing atmosphere to reduce nickel ions adsorbed between MXene layers into nickel element, catalyzing the growth of CNTs; and C2H2 provides a carbon source for the growth of CNTs. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The SEM images of the surface and cross section of the Ni-MWCNTs / MXene composite material with in-situ controlled growth of CNTs in Examples 1 to 3 of the present invention;

[0041] Figure 2 This is a diagram showing the diameter distribution of CNTs in the Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs in Examples 1 to 3 of the present invention;

[0042] Figure 3 The Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs in Examples 1 to 3 of the present invention and the corresponding Ni 2+ -Ti3C2T x Comparative Raman spectra of

[0043] Figure 4 TEM images of Ni-MWCNTs / MXene composite materials with in-situ controlled growth of CNTs in Examples 1 to 3 of the present invention;

[0044] Figure 5 This is a reflection loss diagram of the Ni-MWCNTs / MXene composite material with in-situ controlled growth of CNTs in Application Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0045] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0046] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.

[0047] Example 1

[0048] The preparation method of the Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs includes:

[0049] S1: 400 mesh Ti3AlC2 was etched using an in-situ hydrofluoric acid etching method. Specifically, 40 mL of 9 mol / mL concentrated hydrochloric acid was added to a polytetrafluoroethylene bottle for magnetic stirring. After stirring for 15 minutes, 2 g of LiF was added. After stirring at a constant temperature of 35°C for 15 minutes, 2 g of Ti3AlC2 was slowly added within 10 minutes to prevent rapid addition from causing violent heat release. The etching was performed with magnetic stirring for 24 hours at a rotation speed of 500 rpm and a constant temperature of 35°C.

[0050] S2: Divide the liquid etched in S1 into four centrifuge tubes, wash with deionized water, and collect the precipitate after centrifugation. Repeat the washing 6 to 7 times to make the pH value of the upper clear liquid after centrifugation around 6, and collect the bottom precipitate to obtain multilayer Ti3C2T x The centrifugal speed was 5000 rpm and the time was 5 minutes.

[0051] S3: Multilayer Ti3C2T x After mixing with an appropriate amount of deionized water, ultrasonication was performed in a circulating condensed water constant temperature water bath (-4°C) for 90 minutes, and the upper black liquid was centrifuged to obtain a few-layer Ti3C2T x dispersion, and calculate the concentration of the dispersion by vacuum filtration;

[0052] S4: Use a pipette to measure 1 mL of few-layer Ti3C2T x The dispersion is added to a vacuum filtration device, and after it is completely drained, its mass is weighed to obtain the concentration of the dispersion. The filter membrane used for filtration is Celgard3501.

[0053] S5: Electrophoretic deposition was performed, and the electrolyte for deposition was 3 mg / mol of few-layer Ti3C2T x The working electrode is a 1.5cm×1.5cm nickel sheet, clamped with a graphite clamp. The counter electrode is a graphite electrode, the nickel sheet of the working electrode should face the counter electrode, and the center distance between the working electrode and the counter electrode is 1.5cm. Apply a constant voltage of 2V and the deposition time is 8h. After deposition, put the working electrode into a vacuum oven and dry it at 60℃ for 10h. After drying, tear it off from the nickel sheet to get Ni 2+ -Ti3C2T x .

[0054] S6: The above Ni 2+ -Ti3C2T x Put it in a quartz crucible, and then put the quartz crucible in an alumina ark and send it into a CVD tube furnace for CVD growth of CNTs. Evacuate the chamber at room temperature to make its pressure lower than 100pa, then turn on N2 to restore the chamber to normal pressure to remove other gases in the chamber. After completion, start heating and introduce H2 after N2 purging for 15 minutes, with flow rates of 150sccm and 50sccm respectively. The temperature is increased from room temperature to 400℃ at a heating rate of 5℃ / min and kept warm for 30min, and then increased to 550℃ at a heating rate of 10℃ / min and kept warm for 120min. At the beginning of the insulation at 550℃, C2H2 is introduced and the chamber pressure is maintained at 5×10 4 pa, the gas flow rate was 50sccm, and the gas flow rate of N2 was adjusted to 100sccm, the gas flow rate of H2 remained unchanged, and the total flow rate was 200sccm. After the insulation was completed, C2H2 and H2 were turned off, and the temperature was lowered to room temperature in N2 atmosphere with a flow rate of 200sccm to obtain Ni-MWCNTs / Ti3C2T x , denoted as 2-Ni-MWCNTs / Ti3C2T x .

[0055] Figure 1 a, 1d are 2-Ni-MWCNTs / Ti3C2T obtained in Example 1 x Surface and cross-sectional SEM images.

[0056] Figure 2 a is 2-Ni-MWCNTs / Ti3C2T obtained from Example 1 x Diameter distribution of 100 carbon nanotubes randomly selected from the SEM image.

[0057] Figure 3 a 2-Ni-MWCNTs / Ti3C2T obtained in Example 1 x Raman spectra further show that in Ti3C2T x CNTs are grown on the substrate.

[0058] Figure 4 a is the 2-Ni-MWCNTs / Ti3C2T obtained in Example 1 x HRTEM images of 2-Ni-MWCNTs / Ti3C2T x The average particle size of the obtained Ni particles was 24.26 nm.

[0059] Example 2

[0060] Compared with Example 1, the difference is that the voltage applied during deposition in S5 is 1.5 V. x , denoted as 1.5-Ni-MWCNTs / Ti3C2T x .

[0061] Figure 1 b, 1e are 2-Ni-MWCNTs / Ti3C2T obtained from Example 2 x Surface and cross-sectional SEM images.

[0062] Figure 2 b is 1.5-Ni-MWCNTs / Ti3C2T obtained from Example 2 x Diameter distribution of 100 carbon nanotubes randomly selected from the SEM image.

[0063] Figure 3 b 1.5-Ni-MWCNTs / Ti3C2T obtained in Example 2 x Raman spectra further show that in Ti3C2T x CNTs are grown on the substrate.

[0064] Figure 4 b is the 1.5-Ni-MWCNTs / Ti3C2T obtained in Example 2 x HRTEM images show that 1.5-Ni-MWCNTs / Ti3C2T x The average particle size of the obtained Ni particles was 22.95 nm.

[0065] Example 3

[0066] Compared with Example 1, the difference is that the voltage applied during deposition in S5 is 1 V.x , denoted as 1-Ni-MWCNTs / Ti3C2T x .

[0067] Figure 1 c, 1f are 1-Ni-MWCNTs / Ti3C2T obtained in Example 3 x Surface and cross-sectional SEM images.

[0068] Figure 2 c is 1-Ni-MWCNTs / Ti3C2T obtained from Example 3 x Diameter distribution of 100 randomly selected carbon nanotubes in the SEM image.

[0069] Figure 3 c 1-Ni-MWCNTs / Ti3C2T obtained in Example 3 x Raman spectra further show that in Ti3C2T x CNTs are grown on the substrate.

[0070] Figure 4 c is 1-Ni-MWCNTs / Ti3C2T obtained in Example 3 x HRTEM images show that 1-Ni-MWCNTs / Ti3C2T x The average particle size of the obtained Ni particles was 14.8 nm.

[0071] Example 4

[0072] The preparation method of the Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs includes:

[0073] S1: 400 mesh Ti3AlC2 was etched using an in-situ hydrofluoric acid etching method. Specifically, 40 mL of 9 mol / mL concentrated hydrochloric acid was added to a polytetrafluoroethylene bottle for magnetic stirring. After stirring for 15 minutes, 2 g of LiF was added. After stirring at a constant temperature of 37°C for 15 minutes, 2 g of Ti3AlC2 was slowly added within 10 minutes to prevent rapid addition from causing violent heat release. The etching was performed with magnetic stirring for 24 hours at a rotation speed of 350 rpm and a constant temperature of 45°C.

[0074] S2: Divide the liquid etched in S1 into four centrifuge tubes, wash with deionized water, and collect the precipitate after centrifugation. Repeat the washing 6 to 7 times to make the pH value of the upper clear liquid after centrifugation around 6, and collect the bottom precipitate to obtain multilayer Ti3C2T x The centrifugal speed was 5000 rpm and the time was 5 minutes.

[0075] S3: Multilayer Ti3C2T xAfter mixing with an appropriate amount of deionized water, ultrasonication was performed in a circulating condensed water constant temperature water bath (-4°C) for 90 minutes, and the upper black liquid was centrifuged to obtain a few-layer Ti3C2T x dispersion, and calculate the concentration of the dispersion by vacuum filtration;

[0076] S4: Use a pipette to measure 1 mL of few-layer Ti3C2T x The dispersion is added to a vacuum filtration device, and after it is completely drained, its mass is weighed to obtain the concentration of the dispersion. The filter membrane used for filtration is Celgard3501.

[0077] S5: Electrophoretic deposition is performed, and the electrolyte for deposition is 1 mg / mol of a few-layer Ti3C2T x The working electrode is a 1.5cm×1.5cm nickel sheet, clamped with a graphite clamp. The counter electrode is a graphite electrode, the nickel sheet of the working electrode should face the counter electrode, and the center distance between the working electrode and the counter electrode is 1.5cm. Apply a constant voltage of 2V and the deposition time is 10h. After deposition, put the working electrode into a vacuum oven at 60℃ and dry it for 10h. After drying, tear it off from the nickel sheet to get Ni 2+ -Ti3C2T x .

[0078] S6: The above Ni 2+ -Ti3C2T x Put it in a quartz crucible, and then put the quartz crucible in an alumina ark and send it into a CVD tube furnace for CVD. Evacuate the chamber at room temperature to make its pressure lower than 100pa, then turn on N2 to restore the chamber to normal pressure to remove other gases in the chamber. After completion, start heating and introduce H2 after N2 purging for 15 minutes, with flow rates of 150sccm and 50sccm respectively. The temperature is increased from room temperature to 420℃ at a heating rate of 5℃ / min and kept warm for 30min, and then increased to 580℃ at a heating rate of 10℃ / min and kept warm for 120min. At the beginning of the insulation at 550℃, C2H2 is introduced and the chamber pressure is maintained at 4×10 4 pa, the gas flow rate was 50sccm, and the gas flow rate of N2 was adjusted to 100sccm, the gas flow rate of H2 remained unchanged, and the total flow rate was 200sccm. After the insulation was completed, C2H2 and H2 were turned off, and the temperature was lowered to room temperature in N2 atmosphere with a flow rate of 200sccm to obtain Ni-MWCNTs / Ti3C2T x , denoted as 2'-Ni-MWCNTs / Ti3C2T x .

[0079] Example 5

[0080] The preparation method of the Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs includes:

[0081] S1: 400 mesh Ti3AlC2 was etched using an in-situ hydrofluoric acid etching method. Specifically, 40 mL of 9 mol / mL concentrated hydrochloric acid was added to a polytetrafluoroethylene bottle and magnetically stirred. After stirring for 15 minutes, 2 g of LiF was added. After stirring at a constant temperature of 35°C for 15 minutes, 2 g of Ti3AlC2 was slowly added within 10 minutes to prevent rapid addition from generating violent heat. The etching was performed with magnetic stirring for 30 hours at a rotation speed of 500 rpm and a constant temperature of 35°C.

[0082] S2: Divide the liquid etched in S1 into four centrifuge tubes, wash with deionized water, and collect the precipitate after centrifugation. Repeat the washing 6 to 7 times to make the pH value of the upper clear liquid after centrifugation around 6, and collect the bottom precipitate to obtain multilayer Ti3C2T x The centrifugal speed was 5000 rpm and the time was 5 minutes.

[0083] S3: Multilayer Ti3C2T x After mixing with an appropriate amount of deionized water, ultrasonication was performed in a circulating condensed water constant temperature water bath (-4°C) for 90 minutes, and the upper black liquid was centrifuged to obtain a few-layer Ti3C2T x dispersion, and calculate the concentration of the dispersion by vacuum filtration;

[0084] S4: Use a pipette to measure 1 mL of few-layer Ti3C2T x The dispersion is added to a vacuum filtration device, and after it is completely drained, its mass is weighed to obtain the concentration of the dispersion. The filter membrane used for filtration is Celgard3501.

[0085] S5: Electrophoretic deposition was performed, and the electrolyte for deposition was 5 mg / mol of few-layer Ti3C2T x The working electrode is a 1.5cm×1.5cm nickel sheet, clamped with a graphite clamp. The counter electrode is a graphite electrode, the nickel sheet of the working electrode should face the counter electrode, and the center distance between the working electrode and the counter electrode is 1.5cm. Apply a constant voltage of 2V and the deposition time is 6h. After deposition, put the working electrode into a vacuum oven at 60℃ and dry it for 10h. After drying, tear it off from the nickel sheet to get Ni 2+ -Ti3C2T x .

[0086] S6: The above Ni 2+ -Ti3C2T xPut it in a quartz crucible, and then put the quartz crucible in an alumina ark and send it into a CVD tube furnace for CVD. Evacuate the chamber at room temperature to make its pressure lower than 100pa, then turn on N2 to restore the chamber to normal pressure to remove other gases in the chamber. After completion, start heating and introduce H2 after N2 purging for 15 minutes, with flow rates of 150sccm and 75sccm respectively. The temperature is increased from room temperature to 400℃ at a heating rate of 5℃ / min and kept warm for 30min, and then increased to 550℃ at a heating rate of 10℃ / min and kept warm for 120min. At the beginning of the insulation at 550℃, C2H2 is introduced and the chamber pressure is maintained at 6×10 4 pa, the gas flow rate was 75sccm, and the gas flow rate of N2 was adjusted to 50sccm, the gas flow rate of H2 remained unchanged, and the total flow rate was 200sccm. After the insulation was completed, C2H2 and H2 were turned off, and the temperature was lowered to room temperature in N2 atmosphere with a flow rate of 200sccm to obtain Ni-MWCNTs / Ti3C2T x , recorded as 2"-Ni-MWCNTs / Ti3C2T x .

[0087] Comparative Example 1

[0088] Compared with Example 1, the difference is that the voltage applied during deposition in S5 is 3 V. x , denoted as 3-Ni-MWCNTs / Ti3C2T x .

[0089] Comparative Example 2

[0090] Compared with Example 1, the difference is that the voltage applied during deposition in S5 is 5 V. x , denoted as 5-Ni-MWCNTs / Ti3C2T x .

[0091] Application Examples 1 to 3

[0092] The samples of Examples 1 to 3 were respectively mixed with paraffin wax in a mass ratio of 7:13 in n-hexane, and pressed into coaxial rings with an outer diameter of 7.04 mm and an inner diameter of 3 mm at a pressure of 4 MPa for wave absorption testing.

[0093] Figure 5 a is a 3D reflection loss curve diagram of Example 1 at different thicknesses. Figure 5 b is the 3D reflection loss curve of Example 2 at different thicknesses. Figure 5 c is the 3D reflection loss curve of Example 3 at different thicknesses. Figure 5d is a comparison chart of the best reflection loss of Examples 1 to 3. It can be seen that Example 1 has the best reflection loss of -37.94dB at a thickness of 2.47mm, and the effective absorption bandwidth is 1.54GHz. At the same time, the entire band of C and X can be effectively absorbed by changing its thickness. Compared with Example 3, it can be seen that the wave absorption performance of Example 1 has been greatly improved, and its reflection loss has been improved from -6.37dB to -37.94dB. It shows that the increase in the diameter of CNTs has a significant improvement in its wave absorption performance. The main reason is that Ni-MWCNTs / Ti3C2T x The increase in the diameter of the CNTs tube significantly improves its conductivity, which leads to an increase in the dielectric imaginary part and dielectric loss. Compared with Example 2, Example 1 has a thinner thickness and smaller reflection loss, which meets the requirements of lightweight wave absorption. It can be seen that Example 1 has better wave absorption performance.

[0094] According to the above content, it can be seen that the Ni-MWCNTs / Ti3C2T x All of them showed good wave absorbing performance. x It also exhibits similar morphology and microwave absorption performance as Example 1.

[0095] In Comparative Example 1, due to the increase in voltage, the concentration of dissolved nickel ions in the same time is too high and the ion radius becomes larger, so the content of nickel ions adsorbed between the layers is high, the sites for catalytic growth of CNTs increase, and the diameter of CNTs increases, resulting in excessively high conductivity and poor wave absorption performance. In Comparative Example 2, the voltage is further increased, and the wave absorption performance is further deteriorated.

[0096] The diameter of CNTs in the composite material is too large, which leads to increased conductivity of the composite material, impedance mismatch, and poor absorption performance.

[0097] In this paper, within a certain range, the larger the Ni particle size in the Ni-MWCNTs / MXene composite material, the larger the tube diameter of the CNTs; the larger the tube diameter of the CNTs in the Ni-MWCNTs / MXene composite material, the greater its conductivity. Too large a tube diameter will lead to too high a conductivity, and too high a conductivity will cause the impedance mismatch of the Ni-MWCNTs / MXene composite material, and the wave absorption performance will deteriorate.

[0098] In summary, the present invention provides a method for in-situ regulating the preparation of Ni-MWCNTs / MXene composite materials, and has achieved excellent performance in the field of microwave absorption; the microwave absorption performance of Ni-MWCNTs / MXene composite materials is regulated by in-situ regulating the diameter of CNTs growth; the voltage during deposition is changed to dissolve the Ni sheet to form Ni 2+The different ionic radii ultimately make the Ni-MWCNTs / Ti3C2T x The Ni particles in the composite material that catalyze the growth of CNTs are of different sizes, thereby regulating the diameter of the CNTs; the larger the diameter of the CNTs in the Ni-MWCNTs / MXene composite material, the greater its conductivity; thereby increasing the dielectric imaginary part and dielectric loss, and improving the microwave absorbing performance.

[0099] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A method for preparing a Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs, characterized in that: The preparation method comprises: x The dispersion was used as the electrolyte, the nickel sheet was used as the working electrode, and the graphite electrode was used as the counter electrode. A voltage of 0.1 to 3 V was applied. After deposition for 1 to 20 h, Ni-MWCNTs / Ti3C2T was grown in situ by CVD. x Composite materials.

2. The preparation method according to claim 1, characterized in that: The few-layer Ti3C2T x The preparation method of the dispersion comprises: etching the MAX phase Ti3AlC2 with an in-situ hydrofluoric acid solution, centrifuging a multi-layer Ti3C2T x ; Multilayer Ti3C2T x Mixed with deionized water, ultrasonic stripping and centrifugation, a few layers of Ti3C2T x Dispersion.

3. The preparation method according to claim 1, characterized in that: The few-layer Ti3C2T x The concentration of the dispersion is 1 to 20 mg / mL.

4. The preparation method according to claim 1, characterized in that: The etching time is 1 to 48 hours, the rotation speed is 100 to 2000 rpm, and the temperature is 35 to 45°C.

5. The preparation method according to claim 1, characterized in that: The CVD in-situ growth comprises: exhausting the air in the CVD tube furnace with an inert gas, first performing a first stage of heating, and then performing a second stage of heating; obtaining Ni-MWCNTs / Ti3C2T x Composite materials.

6. The preparation method according to claim 5, characterized in that: The heating rate of the first stage is 1-20°C / min, the insulation temperature is 300-600°C, and the insulation time is 10-120min; N2 and H2 are passed during the first stage of heating, and the flow rates are 100-500sccm and 10-100sccm respectively.

7. The preparation method according to claim 5, characterized in that: The heating rate of the second stage is 5-20°C / min, the holding temperature is 400-700°C, and the holding time is 60-480min; N2, H2, and C2H2 are passed through the second stage heating, and the flow rates are 10-200sccm, 10-100sccm, and 10-100sccm, respectively; and the pressure in the CVD tube furnace is 1×10 4 ~1×10 5 pa.

8. A Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs is loaded with Ni particles and carbon nanotubes, wherein the average particle size of the Ni particles is 10 to 30 nm, and the average tube diameter of the carbon nanotubes is 20 to 50 nm.

9. The Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs according to claim 8, characterized in that: The reflection loss of the Ni-MWCNTs / MXene composite material with in-situ regulated growth of CNTs is -10 to -50 dB at a thickness of 2.47 mm.

10. A microwave absorbing material, characterized in that: It comprises the Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs obtained by the preparation method described in any one of claims 1 to 7 and / or the Ni-MWCNTs / MXene composite material for in-situ controlled growth of CNTs described in any one of claims 8 to 9.